STRUCTURAL HEALTH MONITORING USING AXOUSTIC EMISSION - Shahiron Shahidon; Norazura Muhamad Bunnori (2017)
This book provides useful and informative knowledge on the applications of the acoustic emission technique on reinforced concrete structures. It covers fundamental concepts of acoustic emission, principles of acoustic emission, source localisation, waves and acoustic analysis methods. This book will also encourage both contractors as well as the Public Work Department (JKR) to use the AE technique in structural health monitoring and deepen their understanding on the assessment of concrete superstructures using the AE technique.